Study Komparatif Efektifitas Strategi Pembelajaran Numbered Heads Together dan Jigsaw Pada Mata Pelajaran IPS Materi Dinamika Penduduk Indonesia Kelas VIII SMP Muhammadiyah 4 Sambi Tahun Ajaran 2015/2016 - Suyatno, Eko Agus (2016)
The study was conducted in SMP Muhammadiyah 4 sambi Boyolali. Each learning process should pay attention setrategi that will be used for learning to walk with an active and effective. The purpose of this study was to determine, or to compare the effectiveness of the strategy over Numbered Heads Together with Jigsaw strategy on population dynamics Indonesia material class VIII SMP Muhammadiyah 4 sambiBoyolali Year 2014/2015. This research method is experimental class VIII A and VIII B of SMP Muhammadiyah 4 sambi with enrollment of 40 students. Both classes are used for all experimental class. Mining, experimental class VIII A class that is using a strategy Numbered Heads Together in the learning process and VIII B using Jigsaw strategies in the learning process .. The results of this study concluded that (1) the use of Jigsaw strategy on population dynamics of matter in Class VIII SMP Indonesia Nuhammadiyah 4 Sambi result of his study showed an increase in the amount of 45% of the pre-test 26.36% to 71.36% on the value of post-testnya. (2) Strategy Jigsaw has a 45% yield improvement, strategy Numbered Heads Together has a 22.27% increase in learning outcomes so that the strategy is more effective than the Jigsaw Jigsaw strategy.